Aspects of George Philipp Telemann's Nouvelaux quatuors, in particular their possible influence on the conversations galantes of Louis-Gabriel Guillemain - Oxtoby, Colleen Joy (College of Music, 2015)
The two quartet-collections under consideration appeared within five years of each other, in the same city and, most significantly, for the same new combination of instruments. As the first was the work of an established and prolific composer, and the second, of a younger, lesser-known man with relatively limited output to his credit, I set out in this dissertation to examine the possibility that the one was modelled on the other. Was Guillemain influenced by the Nouveaux Quatuors of Telemann when he composed his Conversations galantes? Georg Philipp Telemann (1681–1767), a North German who typically absorbed foreign elements into his writing-style published what was probably the last of his chamber music in Paris in 1738, under the title Nouveaux Quatuors en Six Suites. They were called ‘new’ in relation to his earlier set, the Quadri, self-published in Hamburg in 1730. Because of their common scoring, and the assumption that the invitation to visit Paris was based on the strength and reception of the Quadri, the two sets were labelled collectively the ‘Paris Quartets’, by Walter Bergmann in the 1960s. The Frenchman, Louis-Gabriel Guillemain (1705–1770) trained as a violinist in Italy, then returned to France where he was later employed at court. In 1743 he too published quartets for the same instruments as had Telemann. These were the Six sonates en quatuors ou conversations galantes et amusantes which also appeared in two groups of six - op. 12 (1743) and op. 17 (1756). The latter was an arrangement of his op. 13 accompanied keyboard sonatas. The former was chosen for this dissertation, being closer in time to the Nouveaux Quatuors and being original rather than an arrangement. It possibly is also the nearest replication, chronologically-speaking, of Telemann’s scoring: that of traverso, violin, viola da gamba or cello, and basso continuo. It has to be noted, however, that Guillemain specifies the viol for the third obbligato line, whereas Telemann offers cello as an alternative. This in itself is of considerable interest. The relatively new quartet emerged towards the end of an era dominated by the solo and trio sonata genres, the addition of a third concertante instrument fleshing out the configuration of the latter.